Assessing heat treatment of chicken breast cuts by impedance spectroscopy. (March 2017) - Schmidt, Franciny C; Fuentes, Ana; Masot, Rafael; Alcañiz, Miguel; Laurindo, João B; Barat, José M
The aim of this work was to develop a new system based on impedance spectroscopy to assess the heat treatment of previously cooked chicken meat by two experiments; in the first, samples were cooked at different temperatures (from 60 to 90 ℃) until core temperature of the meat reached the water bath temperature. In the second approach, temperature was 80 ℃ and the samples were cooked for different times (from 5 to 55 min). Impedance was measured once samples had cooled. The examined processing parameters were the maximum temperature reached in thermal centre of the samples, weight loss, moisture and the integral of the temperature profile during the cooking–cooling process. The correlation between the processing parameters and impedance was studied by partial least square regressions. The models were able to predict the studied parameters. Our results are essential for developing a new system to control the technological, sensory and safety aspects of cooked meat products on the whole meat processing line.